THE IMPACT OF NEW REVENUE CODE UPON ACCOUNTING. - Cohen, A. H. (The Accounting Review, 1956)
The author discusses the impact of new revenue code on accounting. He describes the effects of taxation and tax laws on accounting theory and practice. He discusses the probable effects of changes in taxing rules on accounting practice. He clarifies the possible effects of tax rules on non-tax accounting by way of illustration. He further mentions two new methods which may be used for tax purposes, which are, the double-rate declining balance method and the sum of the years-digits method. He mentions the effects of changes that occur when a taxpayer changes from accrual method of reporting installment sales to the installment method and changes in the selection of fiscal years for tax purposes. He discusses the change that could affect the willingness of taxpayers to change from an accounting method for accounting purposes. He briefly mentions the minor changes which effected in bringing tax accounting closer to financial accounting and code changes which affect accounting indirectly. He mentions the responsibilities of the accounting profession in face of the new internal revenue code.